2021
DOI: 10.1088/1748-9326/ac2526
|View full text |Cite
|
Sign up to set email alerts
|

Cleaner air reveals growing influence of climate on dissolved organic carbon trends in northern headwaters

Abstract: Surface water browning, the result of increasing concentrations of dissolved organic matter (DOM), has been widespread in northern ecosystems in recent decades. Here, we assess a database of 426 undisturbed headwater lakes and streams in Europe and North America for evidence of trends in DOM between 1990 and 2016. We describe contrasting changes in DOM trends in Europe (decelerating) and North America (accelerating), which are consistent with organic matter solubility responses to declines in sulfate depositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 61 publications
3
31
0
Order By: Relevance
“…The causes for the widely observed DOC increased in temperate and boreal lakes are still debated and not within the scope of the present study. It has been suggested that decreasing ionic strength in the soil solution (mainly due to the widespread sulfate decrease) is responsible for an increase in DOC solubility thus increasing its exportation to surface water (Monteith et al 2007;Lawrence and Roy 2021;de Wit et al 2021). In this context, the increasing DOC concentration (and thereby, contribution of organic acids to the inorganic acid anions) could be a consequence of decreasing acid deposition and should then be considered to be part of the "recovery" process instead of slowing it down, although it may likely slow down the rate of ANC and AlcG increases.…”
Section: What Is the Impact Of Doc On The Rate Of Chemical Lake Recov...mentioning
confidence: 99%
“…The causes for the widely observed DOC increased in temperate and boreal lakes are still debated and not within the scope of the present study. It has been suggested that decreasing ionic strength in the soil solution (mainly due to the widespread sulfate decrease) is responsible for an increase in DOC solubility thus increasing its exportation to surface water (Monteith et al 2007;Lawrence and Roy 2021;de Wit et al 2021). In this context, the increasing DOC concentration (and thereby, contribution of organic acids to the inorganic acid anions) could be a consequence of decreasing acid deposition and should then be considered to be part of the "recovery" process instead of slowing it down, although it may likely slow down the rate of ANC and AlcG increases.…”
Section: What Is the Impact Of Doc On The Rate Of Chemical Lake Recov...mentioning
confidence: 99%
“…The change in atmospheric S deposition is not independent of other C pathways and decreases in S deposition across the Northern Hemisphere have been related to increases in loss of DOC in rivers from peat headwaters (de Wit et al, 2021;Montieth et al, 2007); this has also been observed within this study catchment (Clark et al, 2005). If decreasing S deposition is leading to increased loss of DOC from peat catchments, this not only means an increase in the direct loss of C from peatlands but also that deep peat formation may be limited via Equation 14or Equation 22.…”
Section: Discussionmentioning
confidence: 97%
“…Montaith et al [45] believe that this process is related to the role of humic acids at the recovery of the chemical composition of lake waters after their acidification over the past two to three decades. Lately many researchers explained this phenomenon by the additional effect of climate warming [9,27,48,61].…”
Section: Acid Equivalentmentioning
confidence: 99%